2021
DOI: 10.1002/jnr.24986
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala network reorganization mediates the theory of mind performances in multiple sclerosis

Abstract: Theory of mind (ToM) seems to be affected in multiple sclerosis (MS). MRI studies suggested a role of the amygdala in social cognitive performances. Therefore, we explored the role of the amygdala network in ToM using a multimodal MRI approach. In MS, patients with impaired ToM showed contradictory dysexecutive neuropsychological profile. Therefore, we compared neural networks involved in ToM and executive functions (EFs). Twenty patients with relapsing‐remitting MS and 15 matched healthy controls were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In all studies, depression was described as mild because patients with severe symptoms were generally excluded. Several cognitive domains were reported as impaired in patients in MS compared to healthy controls, including executive functions 25 , 26 , semantic fluency 27 , and IQ scores 27 . Three studies 17 , 28 , 29 included depressive and fatigue scores as control variables in their analyses; two of them found that even after controlling for these variables, patients with MS performed significantly worse on aToM 28 and cToM tasks 28 , 29 , one study found no significant influence of these variables on impaired ToM performance 17 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In all studies, depression was described as mild because patients with severe symptoms were generally excluded. Several cognitive domains were reported as impaired in patients in MS compared to healthy controls, including executive functions 25 , 26 , semantic fluency 27 , and IQ scores 27 . Three studies 17 , 28 , 29 included depressive and fatigue scores as control variables in their analyses; two of them found that even after controlling for these variables, patients with MS performed significantly worse on aToM 28 and cToM tasks 28 , 29 , one study found no significant influence of these variables on impaired ToM performance 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies used task-free resting-state functional imaging 26 , 30 , 40 , 46 and three of these studies highlighted the contribution of frontal and temporal networks to aToM impairment in MS. Specifically, they demonstrated a negative correlation between implicit emotion recognition performance and functional connectivity of the fusiform gyrus with lateral occipital gyrus 40 , a positive association between RMET performance and functional connectivity between the left amygdala and frontal pole/paracingulate cortex 26 , or decreased functional connectivity between fronto-temporal regions in patients compared to controls during a facial affect recognition task 30 . On the other hand, Bisecco et al 46 did not find any correlations between the RMET performance and functional connectivity of the default mode, bilateral fronto-parietal executive, salience, cerebellar and limbic networks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, increased rs-fMRI signals have also been observed in various studies. For example, more connectivity recruitment between the amygdala and cerebellar regions and between the amygdala and temporal regions has been detected in multiple sclerosis patients ( Koubiyr et al, 2021 ); in addition, increased nodal centralities in the nodes of the cingulo-opercular network, occipital network, and the ventral lateral prefrontal cortex were detected in Parkinson’s disease patients with MCI ( Hou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%